From World War to Waldheim : culture and politics in Austria and the United States - Good, David F.; Wodak, Ruth, 1950- (Austrian history, culture, and society ;, 1999)
"The growing internationalization of the world poses a fundamental question: through what mechanisms does culture diffuse across political boundaries and what is the role of politics in shaping this diffusion? This volume offers some answers through a case study that examines the relationship between two quite different countries during the cold war - Austria, a small neutral country, and the United States, the reigning superpower